Both Researcher and Second-Generation Witness—On Rescuing Local Memory of the Holocaust in Poland. Issue 2 (May 2019) - Sułek, Antoni
This sketch narrates an account of the author's abundant years of fieldwork, delving into the Holocaust and memory thereof in the Polish countryside. The region selected is highly representative in a phenomenological sense: much of the destiny met by Polish Jews in rural areas played itself out in these lands. Born and raised in this vicinity, the author of the text at hand was able to obtain otherwise inaccessible information about the fate of local Jews, culled from conversations with current and former inhabitants. Moreover, this inquiry was accompanied by engagement: a complementary goal was to reintroduce Polish Jews and the Shoah into the memory of a community and, by the same token, to demonstrate that the rebuilding of memory is possible in contemporary Poland. In consequence, a memory that includes the Jews who used to live in this area is gradually returning to the region under investigation. Among other things, a monument now stands in the village, playing a central role for the community—a wall commemorating murdered local Jews as well as local non-Jewish Poles recognized as Righteous Among the Nations. This provincial society has thus also been prepared to face knowledge about local persecutors and perpetrators of Holocaust crimes against local Jews.